Mekanisme Pembentukan Peraturan Nagari yang Baik (Studi di Nagari Gurun Panjang Kecamatan Bayang Kabupaten Pesisir Selatan Sumatera Barat) - Besse Patmawanti; Naldi Gantika (Universitas Batanghari Jambi, 2020)
This research is descriptive analytic. The method uses in this research is the normative and juridical empiric method. This research is done in Nagari Gurun Panjang Disctrict of Bayang South Pesisir Regency West Sumatera. The techbique of collecting data is interview and document study. Then, the data analyzed qualitatively in descriptive analysis form. The results of research show that: (1) the nagari regulation formed by governance of nagari, consist of BAMUS nagari together walinagari. The existence of nagari regulation in the regulation admitted as one of legal law; (2) the governance of nagari Gurun Panjang has authority and manage his household itself, included in the forming of nagari regulation. The proposal of making nagari regulation can be from walinagari and then discussed between walinagari and BAMUS nagari. After approfing, the nagari regulation then brought by the head of BAMUS nagari to walinagari to be approved (and given to head of regency though head of district; (3) a nagari regulation constists of some parts arranged in a framework. The framework of a nagari regulation concits of six parts; title, introduction, content, closing, explanation (if needed), and attachment (if needed).